A facile synthesis of sub-10 nm Ni2P/g-C3N4 photocatalytic composite with ohmic contact for clean H2-energy generation under visible light irradiation. (20th May 2023) - Xu, Shen; Huang, Jianying; Li, Zengxing; Lei, Yonggang; Zhang, Yingzhen; Ng, Kim Hoong; Lai, Yuekun
Abstract: It is very attractive to find a cheap and efficient cocatalyst for enhancing the H2 generation of graphitic carbon nitride (CN) under visible light. To achieve that, we proposed a novel two-step method to deposit sub-10 nm metallic Ni2 P particles on the surface of CN sheets for a maximized interfacial contact. Characteristic results confirmed the establishment of ohmic heterojunction upon Ni2 P-modification of CN, which deemed to be an effective measure to alleviate photo-charges recombination. In addition to facilitating spatial separation of charges, Ni2 P could also enhance the optical properties of CN while reducing its impedance for interfacial electron shuttling. Better still, the P-end of Ni2 P is highly electronegative, offering desirable H + -capturing capability for enhanced H2 generation. These give rise to an improved H2 production of Ni2 P/CN composite, optimally at 645.3 μmol g −1 ·h −1 as compared to immeasurable H2 yielded by the pristine CN. Such photocatalytic performance is even comparable to the Pt-modified CN photocatalyst (640.6 μmol g −1 ·h −1 ). In recyclability test, a notable activity suppression of 33.17% was recorded after four reaction cycles. This can be ascribed to the pronounced photo-corrosion of the Ni2 P cocatalyst during photoreaction. Nonetheless, a remarkably high H2 generation (1328.6 μmol g −1 in 3 h) was still attained at 4 th cycle. This justifies the effectiveness of our synthesized Ni2 P cocatalyst in enhancing H2 generation of CN under visible light irradiation. Highlights: Sub-10 nm Ni2 P was deposited on g-C3 N4 for enhanced H2 generation. Ohmic contact was successful formed at the interface Ni2 P/g-C3 N4 photocatalyst. 3 wt% Ni2 P/g-C3 N4 prompts comparable H2 generation to 3 wt% Pt/g-C3 N4 .